Experts' successful psychomotor performance was characterized by effective switch of motor and attentional control. (July 2019) - Wang, Kuo-Pin; Cheng, Ming-Yang; Chen, Tai-Ting; Chang, Yu-Kai; Huang, Chung-Ju; Feng, Jie; Hung, Tsung-Min; Ren, Jie
Abstract: Objectives: This study proposed that Mu (8–13 Hz) and SMR (12–15 Hz) readings in the sensorimotor cortical area can be used to investigate the cognitive mechanisms underlying optimal motor performance. Design: This study used a within-subject design. Method: Forty expert golfers were recruited to perform 60 putts while their EEGs were recorded. The putting distance was chosen to ensure that approximately 50% of all putts would be missed so that there was a need for constant adjustments to be made during performance. Successful performance was defined as the ball going in the hole. Results: (a) Lower Mu power in Cz, and alpha power in Pz and Oz were observed for successful performances compared with unsuccessful performances at T1 (−2000 ∼ −1000 ms); (b) Higher SMR power in Cz was observed for successful performances relative to unsuccessful performances at T2 (−1000 ∼ 0 ms). Conclusions: These findings not only support the multi-action plan model (MAP) and the psychomotor efficiency hypothesis, but also reveal the temporal dynamics of the cognitive mechanisms in an optimal-controlled state. Highlights: Successful performance was preceded by lower Mu followed by higher SMR power. A switch from motor to attentional control underpins successful performance. The EEG pattern fits that described as the Type 2 state in the MAP model.